Prevalence of Osteoporosis and Its Associated Factors among Older Men with Type 2 Diabetes. (17th January 2013) - Chen, Hai-ling; Deng, Li-li; Li, Ju-fen
Abstract : This study investigated the prevalence of osteoporosis and its associated factors in old men with T2DM to identify risk factors for low BMD. We enrolled 93 old men (≥60 years of age) with T2DM and 125 healthy old men (controls) and collected data of their lifestyle, medical history, bone densitometry, body weight, height, and blood pressure. Blood samples were collected for biochemical analyses. Urine samples were collected to determine 24 h urinary creatinine, albumin, and protein. Although no differences in age, blood pressure, waist-to-hip ratio, body mass index (BMI), and testosterone levels were observed, the prevalence of low BMD was significantly higher in the T2DM group compared to the control group. The risk of developing low BMD and fracture in T2DM subjects was increased by 46- and 26-fold, respectively, compared to control subjects. BMD of total spine and hip was positively correlated with BMI and negatively correlated with age, duration of diabetes, creatinine, and 24 h urinary albumin. So old men with T2DM have a greater risk of developing low BMD than old men without T2DM.